PENGARUH KECUKUPAN MODAL, KREDIT BERMASALAH, DAN RISIKO PASAR TERHADAP PROFITABILITAS - Nikmatul Choiriyah; Hestin Sri Widiawati; Puji Astuti (Politeknik Negeri Ambon, 2026)
Introduction: The purpose of this research is to analyze how the Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and Net Interest Margin (NIM) impact profitability, indicated by Return on Assets (ROA), specifically within Rural Banks (Bank Perekonomian Rakyat/BPR) located in the Kediri area.Methods: This study used a quantitative approach, relying on secondary data from the 2025 financial reports of Rural Banks released by the Financial Services Authority (Otoritas Jasa Keuangan/OJK). The sample was selected using purposive sampling, resultg of 72 observations that met the specified criteria. The data were analyzed using multiple linear regression in the Statistical Package for the Social Sciences (SPSS) version 25. Before hypothesis testing, we evaluated classical assumptions, including normality, multicollinearity, heteroscedasticity, and autocorrelation, to validate the regression model.Results: The findings show that both the Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) have a positive and statistically significant impact on profitability. At the same time, Non-Performing Loans (NPL) demonstrate a negative and statistically significant effect on profitability. Collectively, CAR, NPL, and NIM significantly affect the profitability of rural banks in the Kediri region.Conclusion and Suggestion: The results indicate that the levels of capital adequacy, the quality of credit, and the capacity to earn net interest income are important determinants of the profitability of Rural Banks. Future studies should include more financial and macroeconomic factors and lengthen the observation timeframe to achieve more robust results. Keywords: Capital Adequacy Ratio; Non-Performing Loan; Net Interest Margin; Profitability; Rural Banks.